Occupational radiation exposure to the thyroid in angiography procedures: single-centre study - Sharani, Nur Fasehah Hani; Shah, Sayed Inayatullah; Rabaiee, Nor Ain (Springer, 2025)
Healthcare professionals express significant concern regarding the potential occupational exposure to ionizing radiation in clinical settings. This study aims to measure and compare the radiation dose to the thyroid of angiography staff during two procedures: percutaneous transhepatic biliary drainage (PTBD) and central venoplasty. The procedures were conducted under the biplane angiography system at the Department of Radiology, Sultan Ahmad Shah Medical Centre @IIUM. The radiologist, medical officer, radiographer, and nurse placed the nanoDot Optically Stimulated Luminescent Dosimeters (OSLDs) inside and outside the thyroid shielding during the procedure. According to the findings, radiation exposure is highest outside the radiologist’s thyroid shielding, with the maximum recorded dose being 1.139 mGy during the central venoplasty procedure. The medical officer received the lowest dose among the four healthcare professionals. The thyroid dose for different healthcare professionals varies significantly due to differences in their standing positions and the duration of the procedures. However, the radiation doses between procedures showed no significant difference (v2(2) = 3.000, p = 0.392). In conclusion, these results emphasise the significance of implementing effective radiation protection measures, especially for radiologists who face the highest risk. Consistent monitoring and adherence to safety protocols are crucial to reducing occupational radiation exposure for all healthcare professionals.